The impact of childhood maltreatment on the severity of childhood-related posttraumatic stress disorder in adults. (October 2021) - Rameckers, Sophie A.; van Emmerik, Arnold A.P.; Bachrach, Nathan; Lee, Christopher W.; Morina, Nexhmedin; Arntz, Arnoud
Abstract: Background: Childhood maltreatment is relatively common and is related to a range of negative consequences, such as Posttraumatic Stress Disorder (PTSD). There are indications that various maltreatment types are related to PTSD severity, although not all types, such as emotional abuse, meet the PTSD Criterion-A. Objective: The aim of the present study was to examine the relationship between 5 types of childhood maltreatment (i.e., sexual, physical, and emotional abuse, and physical and emotional neglect) and the severity of adult PTSD and PTSD symptoms. Participants and setting: Adult participants ( N  = 147) with Childhood-related PTSD (Ch-PTSD) recruited from clinical sites completed the Childhood Trauma Questionnaire-short form (CTQ-sf) and 2 PTSD measures: The Clinician Administered PTSD Scale for DSM-5 (CAPS-5) and the PTSD Checklist for DSM-5 (PCL-5). Methods: Childhood maltreatment predictors and 2 covariates, age and gender, were analysed in multivariate multilevel models as participants were nested within sites. A model selection procedure, in which all combinations of predictors were examined, was used to select a final set of predictors. Results: The results indicated that emotional abuse was the only trauma type that was significantly related to severity of PTSD and to the severity of specific PTSD symptom clusters ( r between 0.130 and 0.338). The final models explained between 6.5% and 16.7% of the variance in PTSD severity. Conclusions: The findings suggest that emotional abuse plays a more important role in Ch-PTSD than hitherto assumed, and that treatment should not neglect processing of childhood emotional abuse. Highlights: Childhood maltreatment is very common and several types are related to PTSD. Only emotional abuse appears to be robustly associated with PTSD severity. The findings were robust across outcomes and separate PTSD symptom clusters.